Multi-agent heterogeneous network selection method based on 5G UAV communication - Yu DING; Chenkai LI; Huimei HAN; Weidang LU; Yuanhong REN; Yuan GAO; Jiang CAO (Dianxin kexue)
The combination of 5G UAV communication and different wireless access technologies makes wireless heterogeneous networks present a diversified development trend.However, various types of service requests by users have different requirements on the heterogeneous networks, which leads to the problem of network selection.A multi-agent heterogeneous network selection method based on 5G UAV communication was proposed.Specifically, the users were divided into multiple agents.From the two aspects of the user side and the network side, the delay and transmission rate requirements of the user side and the load balancing requirement of the network side were comprehensively considered as the relevant parameters of immediate reward.The simulation results show that the proposed heterogeneous network selection method can select the appropriate network according to the needs of users of different service types, balance the load of the network, and make full use of the resources of the heterogeneous wireless network.